Schamanentrachten in Sibirien - Lönnqvist, Bo (Scripta Instituti Donneriani Aboensis, 1987)
The article deals with Shamanic folk costumes originating among the Sami populations of Siberia, analyzing their forms and functions as well as age and historical background.